Perceptions, circumstances and motivators affecting the implementation of contagious bovine pleuropneumonia control programmes in Nigerian Fulani pastoral herds - Suleiman, A.; Jackson, Elizabeth; Rushton, J. (Elsevier, 2018)
Contagious bovine pleuropneumonia (CBPP) is an infectious disease of cattle which substantially contributes to poor productivity of the sub-Saharan pastoral livestock sector. In Nigeria and most of the West African countries, limited public funding for CBPP control have necessitated farmers to bear a bigger burden of managing the disease. Understanding the factors influencing decision of farmers to implement disease control programmes is therefore a key element in informing future policies aimed at improving CBPP management. This study explored perceptions of Nigerian Fulani pastoral herdsmen on the responsibility for cattle healthcare, and identified their circumstances and motivations in implementing CBPP management programmes. Field data were collected from 191 pastoral farmers using a semi-structured, interviewer-administered questionnaire. The results indicated that younger farmers were more likely than their older counterpart to accept the responsibility for CBPP management (p < 0.01). This may signal future prospects for improved CBPP management where upcoming farmers could be encouraged to implement CBPP control programmes and uphold the costs. 13.6% of the farmers had no intention of implementing any CBPP control programme on farm, while 81.2% either had a positive intention or implemented at least one programme aimed at controlling CBPP. Intention to implement CBPP control programmes was significantly associated with educational attainment of farmers (p < 0.01) and their access to CBPP control services offered by trained veterinarians (p < 0.01). Farmers with negative attitudes towards implementing CBPP control programmes could be motivated to change their perspectives by advice from trusted sources and improved access to veterinary services. Conversely, farmers with positive attitudes towards implementing CBPP control programmes were more likely to be motivated by affordable veterinary services and advocacy on specific CBPP control programmes. As such, the former group of farmers will be more likely to benefit from programmes which focus on providing credible information from trusted sources, such as extension agents, veterinarians or successful peers. On the contrary, interventions targeting the latter group of farmers should prioritize cost-effective delivery of improved CBPP control technologies.